Allergic Reactions to Vaccines in Children: From Constituents to Specific Vaccines - Ming-Han Tsai; Chih-Yung Chiu (Biomedicines, 2023)
Vaccination is an essential public health measure that helps to reduce the burden of infectious diseases in children. Although vaccines have an excellent safety record and the association of severe allergic reactions is rare, public concerns about vaccine safety can lead to incomplete vaccination coverage in children with or without allergies. Therefore, it is important to understand the mechanisms and implications of allergic reactions to vaccines and define strategies to manage them to provide the safest care for vaccine recipients. In this review, we provide an overview on the types of allergic reactions that can occur after vaccination, including those caused by various vaccine constituents. We also discuss the mechanisms underlying these allergic reactions and the recommended diagnosis and management strategies for children with a history of suspected allergic reactions to vaccines. An improved understanding of allergic reactions to vaccines can aid in the enhancement of the safety and effectiveness of vaccination.